KOMBINASI BATU PASIR-BENTONIT TERAKTIVASI SEBAGAI ADSORBEN ANION Cr(VI) PADA AIR LINDI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH - Linda, Roza; -, Islamias; Firmansyah, Firdaus (Jurnal Riset Kimia, 2010)
ABSTRACT This research is conducted to know optimum conditions and absorption efficiency of combinated nature bentonite-limestone as anion adsorbent Cr(VI) in lindi of garbage. Batch method was used in this research, and adsorbent was activated using H2SO4 and heating. The result shows that absorption efficiency Cr(VI) in lindi garbage using combinated nature bentonite-limestone is 86.85%. Optimum condition of absorption achieved used adsorbent that have activated with H2SO4 1.6 M and heated temperature 140°C. Keywords: combinated nature bentonite-limestone, lindi, absorption efficiency